Pensamiento crítico y constructivismo: un proceso de reflexión docente - Ballén Martínez, Judy Lizzette (Universidad Antonio Nariño, 2021)
From educative administration, this work looked to recognize how the process of teacher training contributes to strength teaching practices in the College of the Antonio Nariño University, in the town of Usme, Bogotá, articulated to the institutional pedagogical model: constructivist and meaningful learning